Legal Analysis of The Auction Process in The Fiduciary Guarantee Execution System - Habibie, Muhammad; Nugraha, Rais Rahmat; Rangkoly, Mavelda Regina; Maskanah, Ummi (Manunggal Halim Jaya, 2025)
The auction process in the fiduciary guarantee execution system is integral to resolving debt-debt disputes involving movable goods collateral. This research aims to analyze the legal aspects related to implementing auctions in the execution of fiduciary guarantees, which refers to the provisions of Law No. 42/1999 on Fiduciary Guarantees. The main focus of this research is to examine the auction procedure, the rights and obligations of the parties involved, and potential disputes that may arise during the process. In addition, this study evaluates the applicability of precautionary principles and the protection of debtor rights in executing auctions. The analysis results show that although the law has regulated the execution of fiduciary guarantees in detail, some challenges remain, such as unclear auction procedures and potential abuse of authority by creditors. Therefore, this study recommends stricter law enforcement and strengthening supervisory mechanisms in the auction process to protect debtors' rights and achieve justice.